2015
DOI: 10.1007/s10551-015-2675-4
|View full text |Cite
|
Sign up to set email alerts
|

Political Connectedness, Corporate Governance, and Firm Performance

Abstract: In this paper, we present and test a theory of how political connectedness (often linked to political corruption) affects corporate governance and productive efficiency of firms. Our model predicts that underdeveloped democratic institutions that do not punish political corruption result in political connectedness of firms that in turn has a negative effect on performance. We test this prediction on an almost complete population of Slovenian joint-stock companies with 100 or more employees. Using the data on s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
47
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 53 publications
5
47
0
1
Order By: Relevance
“…Concerning the first, we also find evidence that government owned firms and firms owned by financial holding companies, which were in many cases used as a vehicle for a "quick withdrawing of the state from the economy" before the Great Recession, display below average productivity. The findings complement [9] on lower efficiency of government owned companies due to the higher share of politically connected supervisory board members.…”
Section: Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…Concerning the first, we also find evidence that government owned firms and firms owned by financial holding companies, which were in many cases used as a vehicle for a "quick withdrawing of the state from the economy" before the Great Recession, display below average productivity. The findings complement [9] on lower efficiency of government owned companies due to the higher share of politically connected supervisory board members.…”
Section: Introductionsupporting
confidence: 67%
“…On one hand, it is well known that Slovenian privatization process was slow and government owned companies still play an important role in the economy. Due to high interference of political parties in the corporate governance of such companies, their efficiency is lower as in the case of private firms (See [9]). On the other hand, "The plan of the quick withdrawing of the state from the economy", reached in 2006, just before the Great Recession, resulted in a non-transparent privatization which in many cases involved financial holding companies (See [27]).…”
Section: Descriptive Statistics Of Companies and Main Variables Used mentioning
confidence: 99%
“…() and Domadenik et al . () document that bribery and thus corrupt behavior have a negative influence on a firm's sales. According to Beck et al .…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…There is growing empirical evidence to suggest that political connections play an important role in gaining access to formal finance [5], [6], [11], [12]. The most popular proxies for measuring political connectedness in these empirical studies include the proportion of top managers' time spent with public officials, lobbying, frequency of offering bribes and gifts to public officials, holding government contracts, and whether or not top managers' friends and/or family members work at government institutions.…”
Section: Political Connectedness Matters In the Allocation Of Formal mentioning
confidence: 99%
“…For example, using primary survey data, a case study of SMEs in Uzbekistan found that those with government connections were less likely to express a need for external finance, but were more likely to apply for bank credit, and that the application success rate was around 20% higher for politically connected SMEs [5]. Other country-level case studies from Vietnam, Slovenia, and China also found that political connectedness affected the distribution of formal finance [6], [11], [12]. A recent cross-country study based on around 14,000 SME responses from 28 post-communist economies also demonstrates that: (i) the use of interpersonal bureaucratic networks improves the chances of receiving bank credit by up to 8% and (ii) the small share of available SME credit is distributed in favor of those enterprises that capitalize on bureaucratic links.…”
Section: Political Connectedness Matters In the Allocation Of Formal mentioning
confidence: 99%